Pravice in obveznosti delavcev v nestandardnih oblikah dela v sistemu socialnih zavarovanj - Bagari, Sara (Delavci in delodajalci, 2019)
The article addresses the issue of the legal position of nonstandard workers in the Slovenian social insurance system. After defining non-standard workers by observing the existing groups of insured persons, the attention focuses on the regulation of the rights and obligations of these workers in individual social insurance. In this context, the particularities and the adequacy of such arrangements are highlighted as well as the challenges that need to be addressed in the future.
Keywords: nestandardne oblike dela; nestandardni delavci; non-standard forms of work; non-standard workers; sistem socialne varnosti; social insurance; social security system; socialno zavarovanje